Paws for a cause - May, Kyla (2020)
When the local animal shelter can't afford new toys, it's up to Bub and his human, Bella, to save the day. But how could they possibly raise the money? A pet wash, of course! Fun and high jinks abound as Bella and Bub learn that running a pet wash is harder and wetter than it looks. With full-color artwork throughout, this funny and charming diary-format early chapter book is perfect for anyone who believes a furry pal is the best kind of friend.
Keywords: Pug -- Juvenile fiction; Dogs -- Juvenile fiction; Diaries -- Juvenile fiction; Pug -- Fiction; Dogs -- Fiction; Human-animal relationships -- Fiction; Fund-raising -- Fiction; Diaries -- Fiction; Humorous stories; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / Social Themes / Friendship; Diaries; Dogs; Pug; Pug -- Juvenile fiction; Dogs -- Juvenile fiction; Pets -- Grooming -- Juvenile fiction; Fund raising -- Juvenile fiction; Animal shelters -- Juvenile fiction; Toys -- Juvenile fiction; Pug -- Fiction; Dogs -- Fiction; Pets -- Grooming -- Fiction; Fund raising -- Fiction; Animal shelters -- Fiction; Toys -- Fiction; Readers (elementary).; Readers (Elementary); Juvenile works; Fiction; Diary fiction; Humorous fiction; Readers (Publications); Diary fiction; Humorous fiction; Diary fiction; Readers (Publications)